Pengaruh Kinerja Keuangan terhadap Return saham perusahaan Mining and Mining Services terdaftar di Bursa Efek Indonesia Periode 2012-2016 - Hilwa Anggraini; Riri Hanifa; Patmawati Patmawati; Irsan Irsan (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2019)
This study aims to analyze the effect of financial performance on stock returns in mining and mining service companies in the Indonesia Stock Exchange for the period 2012-2016. The research method used is quantitative descriptive. The analysis techniques used in this study are the Classic Assumption Test, Multiple Regression Analysis, t Test and F Test. The sampling technique is purposive sampling. The independent variable used in this study is financial performance. Financial performance intended here is financial performance measured using financial ratios, namely Debt to Equity Ratio (DER), Earning per Share (EPS), Return on Asset (ROA), Net Profit Margin (NPM) and Price Earning Ratio (PER), while the dependent variable is Stock Return. The sample in this study was 20 mining and mining services companies on the Indonesia Stock Exchange in the 2012-2016 study period. Analysis of the data used in this study is multiple linear regression (t test and f test) obtained with SPSS. The results showed that the DER, NPM and PER variables did not affect stock returns and only EPS and ROA variables affected stock return.